Some bounds for the spectral norms of some circulant matrices with generalized Jacobsthal–Lucas numbers - Sukran Uygun (Mathematics Open, 2025)
The purpose of this paper is to investigate the bounds of the spectral norms of some circulant matrices whose elements are a generalization of Jacobsthal–Lucas numbers called bi-periodic Jacobsthal–Lucas numbers by three different ways. We also present the sum of entries; the maximum column sum matrix norm and the maximum row sum matrix norm of this circulant matrices. Then, we evaluate bounds for the spectral norms of Kronecker and Hadamard products of some circulant matrices with bi-periodic Jacobsthal–Lucas numbers. Finally, we give the eigenvalues for circulant matrices with bi-periodic Jacobsthal–Lucas numbers.